De Eendaagsche Express: Kereta Api Cepat di Pulau Jawa, 1929–1942 - Dara Sylvia (Lembaran Sejarah, 2022)
This study discusses about the history of railway in the early 20th century. At the time, the existence of transportation that offered speed and accuracy became a necessity for most people, including in big cities in Java. This is related with massive mobility activities. The number of high speed transportation is limited. Staatsspoorwegen as the state railway company has a idea to operate a high speed railway that can cover a distance of up to 827 kilometers in one day, which became known as the Eendaagsche Express. This article uses historical research methods. In the process, this research uses primary and secondary historical sources, including colonial government documents, magazines, newspapers, advertising catalogs, and other contemporary references. This study founds that the train became a symbol of modernization of transportation in Java, because it was able to revolutionize distance, time, and movement.